Mapping The Heroic Pattern: A Voglerian Analysis of Harry Potter - Irawan, Theresya Mawar Sharon; Natanael, Yolanda Putri; Alisha, Nazwa Nabila; Sinaga, Esther Aprilia (Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the narrative structure of Harry Potter and the Sorcerer’s Stone through the lens of Christopher Vogler’s twelve-stage Hero’s Journey framework, which itself is a modern adaptation of Joseph Campbell’s monomyth theory. Employing qualitative descriptive analysis, the research maps Harry Potter’s development as a mythic hero, beginning with his oppressed life in the non-magical world and culminating in his personal transformation through trials, mentorship, sacrifice, and revelation. The study explores how each stage of Vogler’s structure such as the Call to Adventure, Crossing the Threshold, The Ordeal, and the Return with the Elixir is represented in Harry’s journey. The study also analyzes how supporting characters fulfill archetypal roles like Mentor, Threshold Guardian, Ally, and Shadow, as informed by Jungian psychology. The findings highlight that Harry Potter and the Sorcerer’s Stone is more than a fantasy narrative; it is a psychologically resonant tale of growth and identity shaped by universal storytelling structures.